Analisis Framing Gerakan Sosial: Studi Pada Gerakan Aksi Bela Islam 212 - Riadi, Bagus; Drajat, Diki (Holistik: Journal for Islamic Social Sciences, 2019)
The 212 Movement was once a lively issue being discussed among academics. Each academician has his own perspective in terms of analysis of the emergence of the Islamic Defending Action. One of the highlights of an analysis from Vedi Hadiz which explains that the phenomenon of Islamic Defending Action is actually a formof disillusionment with the failure of the international system. Those who are marginalized then use the vehicle "right populism" as a tool to express injustice. But this article will explain the phenomenon of Islamic Defending Action with framing analysis. Framing is a method of presenting reality in which the truth about an event is not totally denied, but it is subtly deflected, by giving an emphasis on certain aspects (Sukmana, 2016). In general, framing analysis is used in media communication studies. But in this paper the framing approach used is viewed in terms of the social movement approach. The results showed the involvement of the mass media in forming framing related to the factors that led to the creation of a collective identity. A few months before the emergence of the Islamic Defending Action movement, there were important actors such as the GNPF-MUI and FPI who played dominant discourse related to the issue of blasphemy by Ahok. The emergence of the Islamic Action Movement I, II, and III shows the framing carried out to form a collective identity by the movement's actors in framing the events of blasphemy on religion committed by Basuki Tjahaja Purnama. The emergence of the movement then becomes a momentum of consolidation of Muslims in their efforts to fight the hegemony of the global political system which is manifested in the form of government power which in turn will bring up new discourse regarding theÂ #2019GantiPresiden movement